Primordial black holes from fifth forces - Amendola, Luca; Rubio, Javier; Wetterich, Christof (Arxiv, 2017)
Primordial black holes can be produced by a long range attractive fifth force stronger than gravity, mediated by a light scalar field interacting with non-relativistic "heavy" particles. As soon as the energy fraction of heavy particles reaches a threshold, the fluctuations rapidly grow non-linear. The overdensities collapse into black holes or similar screened objects, without the need of any particular feature in the spectrum of primordial density fluctuations generated during inflation. We discuss if such primordial black holes can constitute the total dark matter component in the Universe.
Last revised 23 Apr 2018
Gesehen am 12.11.2020